Highly titled antiferroelectric (R) enantiomers useful for the formulation of eutectic mixtures. Issue 2 (26th January 2020) - Urbańska, M.; Strzeżysz, O.; Szala, M.
ABSTRACT: Novel chiral three-ring ( R ) enantiomers were synthesised using optically active ( R )-(−)-2-octanol. Properties, such as the sequence of phases, the transition temperatures and enthalpies, were tested by a polarising optical microscope and differential scanning calorimeter. An antiferroelectric smectic phase (SmCA *) with a direct transition from the antiferroelectric to the isotropic phase (SmCA *-Iso) was observed for three esters with an achiral C3 F7 CH2 O(CH2 )3 O– terminal chain. Bi- and multicomponent mixtures with a broad temperature range of the antiferroelectric phase and good electro-optical properties were formulated. Helical pitch of pure esters and mixtures was measured by spectrophotometry method. GRAPHICAL ABSTRACT: